2020
DOI: 10.1002/etc.4702
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Pb2+ on Virally Challenged Chicken Macrophage (HD‐11) and B‐Lymphocyte (DT40) Cell Lines In Vitro

Abstract: Elevated levels of lead have been found in waterfowl, due to human activities. Lead may cause immunomodulatory effects, but the mechanisms are largely unknown, especially after viral challenges. To characterize avian immunomodulatory hazards of lead (Pb)2+, we used chicken macrophage (HD‐11) and B‐lymphocyte (DT40) cell lines, as in vitro models for the innate and adaptive immune systems, respectively. The cells were activated via toll‐like receptor‐3 by polyinosinic–polycytidylic acid sodium salt (poly I:C), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…The poly I:C was reported to be recognized by TLR3, triggering several pathways such as nuclear factor κB (NF‐κB) and interferon receptor factors (IRFs) pathways, resulting in generation of a spectrum of cytokines including proinflammatory cytokines (e.g., IL‐8 and IL‐18) via the NF‐κB pathway and antiviral type I IFNs (IFN‐α and ‐β) via IRFs pathways (Alexopoulou et al, 2001; Moynagh, 2005; Sen & Sarkar, 2005; Kawasaki & Kawai, 2014). Our results demonstrated a significant increase in IFN‐α levels due to Hg 2+ exposure in both cell lines, especially DT40 cells (Figure 6C and D), similar to what was observed in Pb 2+ ‐exposed HD‐11 and DT40 cells (Han et al, 2020). Although the expression of type I IFNs was documented to be lifted in HD‐11 cells after 2 h of incubation with poly I:C (Peroval et al, 2013), different IFN‐α levels after poly I:C activation were not found in the qPCR or the ELISA assays after 24 h of exposure in the present study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The poly I:C was reported to be recognized by TLR3, triggering several pathways such as nuclear factor κB (NF‐κB) and interferon receptor factors (IRFs) pathways, resulting in generation of a spectrum of cytokines including proinflammatory cytokines (e.g., IL‐8 and IL‐18) via the NF‐κB pathway and antiviral type I IFNs (IFN‐α and ‐β) via IRFs pathways (Alexopoulou et al, 2001; Moynagh, 2005; Sen & Sarkar, 2005; Kawasaki & Kawai, 2014). Our results demonstrated a significant increase in IFN‐α levels due to Hg 2+ exposure in both cell lines, especially DT40 cells (Figure 6C and D), similar to what was observed in Pb 2+ ‐exposed HD‐11 and DT40 cells (Han et al, 2020). Although the expression of type I IFNs was documented to be lifted in HD‐11 cells after 2 h of incubation with poly I:C (Peroval et al, 2013), different IFN‐α levels after poly I:C activation were not found in the qPCR or the ELISA assays after 24 h of exposure in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Compared with other trace metal ions, Hg 2+ has a relatively high toxicity. For example, the toxicity of lead (Pb) 2+ was evaluated in the same cell types with much higher EC50 values, namely, 480 μM for HD‐11 macrophages and 1700 μM for DT40 lymphocytes (Han et al, 2020 ). Therefore, although inorganic Hg 2+ is generally regarded to be less toxic than MeHg, it could still be a trace metal ion of concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lead inhalation in sensitized guinea pigs was shown to alter IFN-γ/IL-4 ratio, being indicative of reduction in Th1/Th2 balance ( Boskabady et al, 2012 ). Pb 2+ was also shown to be toxic to both B-lymphocytes and especially macrophages, also resulting in reduced IFN-γ production and causing aberrant immune response to viral and bacterial pathogens ( Han et al, 2020 ). These findings corroborate the observed inverse correlation between blood lead levels and T cell count in Pb-exposed subjects ( Mishra et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the added concentrations of Pb 2+ selected for this study do not cause overt cell death on their own, they are associated with alterations in other markers of cellular health at these low levels. 14,[32][33][34] It is crucial that we understand how co-exposures may exacerbate specic cellular mechanisms that may lead to the observed additive toxicity. An in-depth knowledge of the pathways that become disrupted in the context of specic chemical mixtures is essential to the eld of predictive toxicology in mixture work.…”
Section: Mixtures Containing Fccp or Rured And Fccp Increase Cytotoxi...mentioning
confidence: 99%